Time-course responses of circulating microRNAs to three resistance training protocols in healthy young men - Cui, Shufang; Sun, Biao; Yin, Xin; Guo, Xia; Chao, Dingming; Zhang, Chunni; Zhang, Chen-Yu; Chen, Xi; Ma, Jizheng (Scientific reports, 2017)
Circulating microRNAs (c-miRNAs) in human plasma have been described as a potential marker of exercise. The present study investigated the effects of three acute resistance training (RT) protocols on the time-course changes of the c-miRNAs profiles in young males. The subjects (n = 45) were randomly divided into three groups: muscular strength endurance (SE), muscular hypertrophy (MH) and maximum strength (MS). Venous blood samples were obtained before exercise and immediately, 1 h and 24 h after each RT protocol to assess the following biological parameters: c-miRNAs, anabolic and catabolic hormones, inflammatory cytokines and muscle damage markers. The results revealed that the levels of two c-miRNAs (miR-208b and miR-532), six c-miRNAs (miR-133a, miR-133b, miR-206, miR-181a, miR-21 and miR-221) and two c-miRNAs (miR-133a and miR-133b) changed significantly in response to the SE, MH and MS protocols ( p < 0.05), respectively. The nature and dynamic processes of the c-miRNAs response were likely influenced by the RT modality and intensity. Moreover, miR-532 was negatively correlated with insulin-like growth factor-1 and positively correlated with interleukin-10, whereas miR-133a was negatively correlated with cortisol and positively correlated with testosterone/cortisol. These findings suggest that these c-miRNAs may serve as markers for monitoring the RT responses.